IMPROVING TEACHING ASSIGNMENTS THAT TEACH STUDENTS TO READ AND UNDERSTAND IN PRIMARY EDUCATION (Web of Teachers: Inderscience Research, 2024)
This article discusses the importance of teaching students to read and understand reading in primary education, the content, characteristics, the role and methods of further improving their learning assignments in education and in the student's hierarchy.